Riesgos financieros después de la crisis subprime - Leiva Büchi, Rodrigo (2009)
The subprime financial crisis revealed some of risks that were not considered as a priority. Among others, a liquidityrisk is now considered as one of the main risks to work with by all institutions. Apart from that, it became obviousthat traditional risk management focused only on what was known and expected, ignoring analysis and testing eventswith low probability but high impact. Lastly, the subprime crisis left a number of lessons in relation to the regulationfor financial markets that must be considered when creating a new regulatory system.